STUDI KAPASITAS DRAINASE PADA JALAN TANJUNG LIMAU MUARA BADAK - hril, Syak (KURVA S JURNAL MAHASISWA, 2014)
Drainage is functioning waterworks take care of the quality of ground water in its bearing with silinitas and also lessen excess of water coming from rain, seep result of dismissal of town is rest of settlement. Drainage JalanÂ Tanjung Limau Muara Badak is often flood stricken by rain season so that bother traffic fluensy, So that needed action which quickly and precisely in handling rainwater and often result floods area.Method used to calculate rainfall is Methode Of Gumbel, while to count debit drainage channel with Method Of Rational.From result of calculation can be concluded, accomodated floods debit Jalan Tanjung Limau Muara Badak repeat 25 year equal to 2,4096 m3/sec. Consist of maximum rainwater debit 2,3583 m3/sec. Discard debit and irrigant resident 0,0513 m3/sec.Â Â